Generation Z Decision to Use E-Wallets and Its Drivers - Roosdhani, Mohamad Rifqy; Arifin, Samsul; Komaryatin, Nurul; Ali, Ali; Huda, Nurul; Khoiruddin, Muhammad (Economics and Business Solutions Journal, 2025)
The rapid growth of e-wallet technology is reshaping financial transaction behavior, particularly among Generation Z. However, many e-wallet providers struggle to ensure long-term adoption and continued use, due to limited comprehension of the cognitive and psychological factors that drive user decisions in this demographic. This study addressed the gap by empirically analyzing how perceived usefulness and user attitude determine the usage decision of e-wallet services among Generation Z, a technologically adept yet under-researched segment. This study's innovation is found in examining the indirect pathway of perceived usefulness influencing usage decisions through user attitude within a Generation Z context. Employing a quantitative approach, primary data were collected from 125 Generation Z e-wallet users using an online questionnaire.   The data was analysed using partial least squares structural equation modelling, or PLS-SEM.)  through SmartPLS 4.0, testing three key constructs: perceived usefulness, attitude toward use, and usage decision. The findings demonstrated that perceived usefulness had a significant positive effect on both user attitude (coefficient = 0.814, p < 0.05) and usage decision (coefficient = 0.351, p < 0.05). Furthermore, user attitude was found to be a strong predictor of usage decision (coefficient = 0.588, p < 0.05) and served as a significant mediator, with an indirect effect of perceived usefulness on usage decision (coefficient = 0.479, p < 0.05). 80.5% of the variation was explained by the model in usage decision, underscoring its high explanatory power. In conclusion, the study establishes that perceived usefulness is fundamental in shaping positive user attitudes and subsequent e-wallet adoption decisions among Generation Z, emphasizing the mediating role of attitude in the technology acceptance process. These insights inform both theoretical frameworks of technology acceptance and practical strategies for e-wallet providers to boost user engagement and retention.
Keywords: perceived usefulness; attitude; usage decision; Generation Z; e-wallet adoption